Effects of structural Change on trade exchange between Morocco and Atlantic Africa. - (:unkn) unknown (My University, 2025)
In the post-covid19 context, following the effects of the crisis and supply chain imbalances, economic policy choices are based on self-sufficiency and economic sovereignty. Regional integration and concentration in economic blocs is becoming a tool for overcoming unpredictable shocks. This article aims to assess the effects of industrialization and structural change in Atlantic African countries on trade dynamics with Morocco. This developmental approach was formalized in Morocco's Atlantic Initiative to integrate the Sahel countries. Empirically, using an augmented gravity model (GMM system), we will estimate the effects for a sample of 12 countries over a period from 2006 to 2022. The main conclusion of the research, resulting from the model's estimation, is that the dynamics of trade between Morocco and African countries is beneficial for structural transformation and productivity growth, taking advantage of the effect of technology transfer through FDI.Keywords : Structural change, trade exchanges, regional integration, Atlantic Africa
Keywords: African Research